Globalization and its Impact on the Third World Economy - Sharma, Neelam Kumar (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Globalization is a controversial issue in the third world countries. ! is study tries to determine the factors associated with this controversy and explained the economic impacts of globalization in the third world countries on the basis of some of the scholars' arguments expressed on the subject. In the recent past, there have been the pros and cons of globalization in developing countries. Some argue that globalization is indeed a necessary evil to the third world countries that it can neither be rejected nor fully applied to its national policy. However, many others suggest that globalization should be looked at in all its manifestations and from different angles. In order to address this issue, when considered from the economic point of view, the negative economic impacts of globalization should be minimized and exportable capacity of the third world economy in the global market should be increased in a step by step manner. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10465 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 21-28